2008
DOI: 10.1016/j.jneuroim.2008.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sympathectomy increases susceptibility to ocular herpes simplex virus type 1 infection

Abstract: The cornea is one of the most highly innervated tissues in the mammalian host. We hypothesized changes to cornea innervation through chemical sympathectomy would significantly alter the host response to the neurotropic viral pathogen, herpes simplex virus type 1 (HSV-1) following ocular infection. Mice treated with 6-hydroxydopamine hydrobromide displayed reduced tyrosine hydroxylase-positive fibers residing in the cornea. Sympathectomized mice were also found to show a transient rise in virus recovered in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Because 6-OHDA treatment can greatly modify innate immune responses (13,16), this could contribute to the differences between our findings and those of Bonneau and colleagues (25). Using a different HSV model system in mice, Carr and colleagues (26) reported that 6-OHDA treatment before ocular infection does not significantly modify T CD8ϩ responses in draining lymph nodes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Because 6-OHDA treatment can greatly modify innate immune responses (13,16), this could contribute to the differences between our findings and those of Bonneau and colleagues (25). Using a different HSV model system in mice, Carr and colleagues (26) reported that 6-OHDA treatment before ocular infection does not significantly modify T CD8ϩ responses in draining lymph nodes.…”
Section: Discussionmentioning
confidence: 51%
“…As described by van Endert and colleagues (23), peptide determinants are rapidly liberated from the fusion protein by Ub-hydrolases and behave like cytosolic minigene products. 6-OHDA treatment increased the primary T CD8ϩ response to Ova 257-264 and to the immunodominant VV determinant B8R [20][21][22][23][24][25][26][27] (Fig. 2B).…”
Section: -Ohda Treatment Of Host But Not Tcd8؉ Donor Enhances Antiviralmentioning
confidence: 92%
“…Activation of latent VZV causes inflammatory destruction of corneal nerves, 196 whereas inflammation-related neuropeptides can be beneficial in reducing herpetic keratopathies. Trigeminal and corneal sympathetic nervous system activity and increased interferon-γ levels ward off infection in mice, 212 thus preserving corneal nerves. Combination treatment with SP and IGF-1 completely resolves epithelial defects in neurotrophic keratopathy patients, though SP may worsen microbial keratitis by promoting excess inflammation.…”
Section: Corneal Nerve Dysfunctionmentioning
confidence: 99%
“…Combination treatment with SP and IGF-1 completely resolves epithelial defects in neurotrophic keratopathy patients, though SP may worsen microbial keratitis by promoting excess inflammation. 72,212,230 Non-infectious disease processes, both corneal and systemic, also negatively affect corneal nerves.…”
Section: Corneal Nerve Dysfunctionmentioning
confidence: 99%
“…Specifically, A5(ϩ) neurons support HSV-2 replication whereas KH10(ϩ) neurons support HSV-1 productive infection (3). Since A5(ϩ) neurons are noradrenergic (34) and KH10(ϩ) neurons are sensory in nature (8) and both adrenergic and sensory neuronal pathways influence the host immune response or sparing of neurons following HSV infection (14,35), it is not surprising that disparate immune responses to these two closely related but distinct viral pathogens ensue within the nervous system. A randomized, double-blind HSV vaccine trial utilizing glycoprotein D from HSV-2 (gD-2, with alum and 3-O-deacylated monophosphoryl lipid A as an adjuvant) was recently performed to test for efficacy against HSV-1 and HSV-2 genital disease and infection.…”
Section: A) As Well As Cd4mentioning
confidence: 99%